2017
DOI: 10.1177/1465116516678080
|View full text |Cite
|
Sign up to set email alerts
|

What’s Islam got to do with it? Attitudes toward specific religious and national out-groups, and support for EU policies

Abstract: Previous studies predicted European Union attitudes using anti-immigrant attitudes, but without explicitly accounting for attitudes toward different out-groups. We propose that group-specific attitudes independently predict attitudes toward the European Union, but only when the out-group is linked to the European Union issue in question. We additionally argue that realistic or symbolic threat associated with specific outgroups determines whether utilitarian or identity considerations are more important in pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…There is ample evidence for the connection between anti‐EU and anti‐immigrant attitudes (Azrout & Wojcieszak, ; de Vreese & Boomgaarden, ). The tension between immigration policies of the EU and national interest was the core argument for Brexit (Meleady, Seger, & Vermue, ), and disidentification with Europe predicted higher anti‐immigrant sentiments around the time of the Brexit referendum (Abrams & Travaglino, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence for the connection between anti‐EU and anti‐immigrant attitudes (Azrout & Wojcieszak, ; de Vreese & Boomgaarden, ). The tension between immigration policies of the EU and national interest was the core argument for Brexit (Meleady, Seger, & Vermue, ), and disidentification with Europe predicted higher anti‐immigrant sentiments around the time of the Brexit referendum (Abrams & Travaglino, ).…”
Section: Discussionmentioning
confidence: 99%
“…Threat perceptions, in turn, often depend on perceptions of who immigrants are. Public opinion distinguishes among immigrants according to their level of education or job skills (Hainmueller and Hiscox, 2010); reason for immigrating (Blinder, 2015); and racial, ethnic, national, or religious identities (Bansak et al., 2016; Ford, 2008; Gorodzeisky and Semyonov, 2016), all of which may relate to the degree and nature of threats that people perceive from immigration (Azrout and Wojcieszak, 2017).…”
Section: Explaining European or Eu Inclusionismmentioning
confidence: 99%
“…Scholars have found that anti‐immigrant sentiments and stereotypes are actually a key predictor to explain contestation on EU integration (De Vreese & Boomgaarden ; Hobolt et al. ; Azrout & Wojcieszak ; Kentmen‐Cin & Erisen ) and support for exclusionary asylum policies (Canetti et al. ).…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%